Heat Transfer Simulation Study of Cooling Fin Units in Personal Computer Processors Using the Finite Element Method - Refky Jamal (International Journal of Mechanical Computational and Manufacturing Research, 2020)
Everyone would want convenience in completing the work in his life, be it light work or heavy work that is high risk. As we all know, today's technology is so fast that it can replace human jobs where all human work wants to be completed with the results we want. Machines are one example of the application of technology that has a major role in our lives, where an energy, such as electrical energy is converted into motion energy that produces a business in its use. Machines are always evolving because the types of work that are increasingly diverse are always looking for new alternatives in an effort to make the job easier. Of the many types of construction conveyance or conveyor machinery is one End. While the lowest is the AMD parallel fin unit with copper material of 0.00417 K/mm. From the three histogram images above, it can be concluded that the circular fin type with 2024-T3 aluminum material has a better ability to conduct heat than other types of fins and materials. And the AMD parallel fin type with Copper Annealed material is not good at conducting heat. From the operation of the simulation program Visual Nastran 2004 that has been made, several conclusions can be drawn, namely: (1) Study of the performance of the fin unit in dissipating the heat of the processor on a personal computer (PC) operating in the temperature range of 298 – 303 K. The type of fin used for research these are: (a) AMD parallel fins. (b) Parallel fins. (c) Circular fin. (a) AMD parallel fins. (b) Parallel fins. (c) Circular fin. (a) AMD parallel fins. (b) Parallel fins. (c) Circular fin.